Development of a hybrid reflective micro learning model based on ICT in Micro Teaching courses - Faisal, Emil El; Safitri, Sani; Dianti, Puspa; Lestari, Dea; Sulkipani, Sulkipani (Universitas Negeri Yogyakarta, 2024)
This research aims to develop a hybrid reflective micro-teaching model. The research method used is a type of research and development referring to the Borg and Gall R&D Cycle. The research results from reflection sheets indicate that some students could perceive the teaching for themselves. This is evidenced by the correspondence between friend's assessments and the results of their reflections. However, some students seemed less attuned to what was being taught. Peer observations and reflection on students' learning indicate a promising potential for improvement in students' self-assessment. For instance, some students reflected